2011
DOI: 10.1007/s10147-011-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcome of breast cancer patients with 10 or more metastasized axillary lymph nodes

Abstract: Cases of breast tumors with extensive nodal metastasis were found to be heterogeneous in terms of prognosis. History of previous neoadjuvant chemotherapy and higher numbers of metastatic lymph nodes were found to be the two most important prognostic markers for pathologic N3a disease. New strategies such as biologic therapy and novel combinations should be considered for application in patients with poor prognosis, rather than conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[7][8][9] In previous reports, which used older treatment schemes regarded as suboptimal compared with current standard treatment, an approximately 40% 5-year OS was detected in patients with 10 ALN metastases. In a recent report of patients who had 10 ALNs positive for disease and were treated between 2002 and 2012, the rate OS was higher than previously reported as 69.8% at 5 years, but DFS was still disappointing as 46.2%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[7][8][9] In previous reports, which used older treatment schemes regarded as suboptimal compared with current standard treatment, an approximately 40% 5-year OS was detected in patients with 10 ALN metastases. In a recent report of patients who had 10 ALNs positive for disease and were treated between 2002 and 2012, the rate OS was higher than previously reported as 69.8% at 5 years, but DFS was still disappointing as 46.2%.…”
Section: Discussionmentioning
confidence: 97%
“…Several reports have shown an approximately 40% 5-year overall survival (OS), although this estimate was on the basis of old treatments. [7][8][9] The current accepted systemic management of pN3 breast cancer is taxane-based chemotherapy with endocrine therapy in hormone receptor-positive patients. 10 Additionally, trastuzumab should be used in patients who are HER2-positive on immunohistochemistry (IHC) examination.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 19 found that the addition of radiotherapy to other treatment did not improve the dfs of patients with breast cancer at stage pN3 (44.4% vs. 40.3%, p = 0.618) and that the lrr rate was still as high as 26.3%. In addition, Chang et al 20 and Koca et al 21 reported that the 5-year lrr rate was 13%-24% in patients with breast cancer at stage pN3 after pmrt, and the 5-year dfs was only about 46%.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with stage IIIC disease are considered to have pathologic nodal status N3 (pN3; metastases in 10 or more axillary lymph nodes; or in infraclavicular [level III axillary] lymph nodes; or in clinically detected ipsilateral internal mammary lymph nodes in the presence of 1 or more positive level I, II axillary lymph nodes; or in more than 3 axillary lymph nodes and in internal mammary lymph nodes with micrometastases or macrometastases detected by sentinel lymph node biopsy but not clinically detected; or in ipsilateral supraclavicular lymph nodes), regardless of tumor size (T stage), according to the 6th and 7th American Joint Committee on Cancer Tumor Node Metastasis (AJCC TNM) staging system [78]. However, the nodal stage of breast cancer, which classifies disease according to the number of metastatic axillary nodes, is further subdivided into prognostic subgroups based on pathologic and molecular characteristics [91011]. …”
Section: Introductionmentioning
confidence: 99%